Synthesis of 3-Benzylphthalide Derivatives by Using a TDAE Strategy - Ibrahimi, Maroua; Khoumeri, Omar; Abderrahim, Raoudha; Terme, Thierry; Vanelle, Patrice (Synlett, 2020)
A one-pot synthesis of new 3-benzylphthalide derivatives was developed by using a strategy based on tetrakis(dimethylamino)ethylene (TDAE). The reactions in the presence of TDAE of substituted benzyl chlorides with methyl 2-formylbenzoate or of substituted methyl-2-formylbenzoates with 4-nitrobenzyl chloride furnished the corresponding isobenzofuran-1(3H)-one products in moderate to good yields.
Keywords: benzylphthalides; methyl formylbenzoate; nitrobenzyl chlorides; isobenzofuranones